Strategic aspects of innovation policy implementation in the region on the example of the Khabarovsk region - L. V. Konoshko (Вестник университета, 2021)
The implementation of innovation policy at the regional level requires a strategic approach, and the formation of effective strategic responses to suddenly emerging external threats and challenges is particularly important now. In the article the author reflects the results of the study of the specifics of the strategic aspects of the implementation of the innovation policy of the Khabarovsk region in modern conditions and concludes that it is necessary to improve the mechanisms for adjusting the strategic goals of innovative development at the regional level in a rapidly changing external environment. The purpose of the study is to form the current strategic priorities for the  implementation of innovation policy in the region on the example of the Khabarovsk region. As the main methods, the author used SWOT analysis, a  polygon of alternatives, and goal tree have been used.